Individualism and Collectivism in Pro-Environmental Behavior of an Environmentally Educated Community (Case Study of Bendungan Village, Bogor, Indonesia) - Wiradimadja, Dafi Dinansyah; Mori, Hisatsuna; Rizkiah, Riza (Technium Education and Humanities, 2024)
The major element impacting environmental sustainability is the public's lack of awareness about the importance of maintaining and caring for the environment. Minimising environmental damage can be achieved by individuals by engaging in more positive behaviours, such as not littering, becoming rescue volunteers, and raising environ-mental awareness. This will help alleviate psychological problems, like low levels of satisfaction with environ-mental conditions. Using natural resources efficiently and implementing environmentally friendly development are two of the primary goals of environmental management, yet this is incorrect. Pro-environmental behavior refers to a deliberate activity taken to reduce the adverse effects caused by hu-man activities in one's surroundings. Pro-environmental behavior refers to the degree to which behavior affects the accessibility of natural resources or energy from the environment. Engaging in pro-environmental conduct is a beneficial action that helps to reduce environmental harm and enhance environmental conditions and behavior. The Bendungan village where this research is conducted has been educated and informed by the government by its Ecovillage program. The program has successfully educated the village people to be environmentally friendly, especially regarding waste management. This research is conducted using mix methods and questionnaires using the Slovin formula to determine the number of samples. The research showed that individualist values from surpassing collective values and exerting dominance over the majority of village people, internalization of behavior failed to establishing norms and policies that prioritize a more collectivist orientation. Furthermore, it is imperative to have a collective dedication in order to effectively execute these measures. Only a minority of individuals in research location properly dispose waste. Properly disposing waste enhances an individual's self-assurance when donning it, but most individuals in this research location chose not to done it. Different approach besides, education needed to mitigate littering and to promote pro environmental behavior for a community that already have adequate and basic knowledge for environmentally friendly behavior. Internalization approach, although a long process is needed to solve individualism behavior that are endangering the environment. Knowledge and information, based on this research does not correcting people behavior. This research also showed that knowledge does not determining individualism behavior and collectivism behavior has not over-come the power of individualism in this village.